1993
DOI: 10.1152/ajpendo.1993.264.3.e373
|View full text |Cite
|
Sign up to set email alerts
|

Exercise training and clenbuterol reduce insulin resistance of obese Zucker rats

Abstract: This study compared the effects of aerobic exercise training and chronic administration of the selective beta 2-adrenergic agonist clenbuterol on whole body and skeletal muscle insulin resistance in obese (fa/fa) Zucker rats. Obese rats were randomly assigned to training, clenbuterol, or sedentary control groups. Lean littermates served as a second control group. After 4-5 wk of treatment, an oral glucose tolerance test was performed, followed 1 wk later by hindlimb perfusion, during which time the rates of gl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
45
0

Year Published

1995
1995
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(49 citation statements)
references
References 5 publications
4
45
0
Order By: Relevance
“…Hyperinsulinemic human beings and rodents submitted to different types of exercises show reduction of blood insulin levels, even though the decrease rate depends on duration and intensity of training (Torgan et al 1993, Kretschmer et al 2005. It has been suggested that decrease in fat tissue accumulation is related to normalization of fasting insulin levels and, it is well known, insulin has been identified as an adiposity signal, like leptin (Schwartz & Porte 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperinsulinemic human beings and rodents submitted to different types of exercises show reduction of blood insulin levels, even though the decrease rate depends on duration and intensity of training (Torgan et al 1993, Kretschmer et al 2005. It has been suggested that decrease in fat tissue accumulation is related to normalization of fasting insulin levels and, it is well known, insulin has been identified as an adiposity signal, like leptin (Schwartz & Porte 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In another animal model (insulin-resistant obese Zucker rat), clenbuterol did not affect GLUT4 protein and mRNA in red and white skeletal muscle (38,52) but improved glucose tolerance (64). On the other hand, glucose uptake and transport were not different in different muscle fiber types between clenbuterol-treated obese and control obese rats (64 -66).…”
Section: R379mentioning
confidence: 92%
“…In contrast to these unusual responses of clenbuterol treatment with respect to changes in PGC-1␣ mRNA (19,47), our present results are consistent with studies showing that in skeletal muscle, clenbuterol decreases mitochondrial enzyme activity and contents and increases glycolytic enzyme activity (present study; 35,49,53), and our observed reduction in PGC-1␣ protein and mRNA is fully consistent with such changes. Also, long-term clenbuterol administration decreased ␤-adrenergic receptor concentration in skeletal muscle (64,65), effects that may inhibit the transcription of PGC-1␣, thereby contributing to reduced mitochondrial content and capacity in skeletal muscle. Thus, clenbuterol-induced ␤2 adrenergic stimulation by a single injection appears to increase PGC-1␣ transcription (24,48), whereas in the current study, 3 wk of clenbuterol administration decreases PGC-1␣ protein and mRNA, presumably via the decreased ␤2 adrenergic stimulation due to long-term clenbuterol administration (64,65).…”
Section: R381 Clenbuterol Reduces Mitochondrial Substrate Oxidationmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, in the next series of experiments we assessed the impact of the amelioration of insulin resistance and the reduction in the levels of insulinaemia on the amounts of farnesylated p21Ras. One group of Zucker rats (Table 1, Group 4) was exercised for 7 weeks, 90 min per day, whereas another group of Zucker rats (Table 1, Group 5) was treated with clenbuterol, a beta-adrenergic agonist that has previously been shown to improve insulin sensitivity in Zucker rats [16,17]. Both exercise and the treatment with clenbuterol reduced the levels of insulinaemia in obese Zucker rats ( Table 1).…”
Section: Resultsmentioning
confidence: 99%